The Influence of Servant Leadership, Self-Awareness, and Organizational Citizenship Behavior on Employee Performance In Badan Perencanaan Pembangungan Daerah Provinsi Jawa Timur - Patria, Rio; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to examine the influence of servant leadership, selfawareness, and organizational citizenship behavior on employee performance at Badan Perencanaan Pembangungan Daerah Provinsi Jawa Timur. The research was conducted using a quantitative approach and data were collected through questionnaires distributed to employees. The data obtained was analyzed using the Structural Equation Modeling (SEM) PLS method using Smart PLS Version 4.0 software. The respondents used in this study were 79 employees out of a total of 97 employees at Badan Perencanaan Pembangungan Daerah Provinsi Jawa Timur. The data collection instrument measured on a Likert scale. The findings revealed that servant leadership, selfawareness, and organizational citizenship behavior have a significant positive influence on employee performance. These results highlight the importance of fostering servant leadership qualities, promoting self-awareness, and encouraging organizational citizenship behavior in improving employee performance at Badan Perencanaan Pembangunan Daerah Provinsi Jawa Timur.